Pro HTML5 and CSS3 design patterns - Bowers, Michael; Synodinos, Dionysios .; Sumner, Victor; SpringerLink (Online service). (Berkeley, CA Apress, 2011)
Pro HTML5 and CSS3 Design Patterns is a reference book and a cookbook on how to style web pages using CSS3 and HTML5. It contains 350 ready to use patterns (CSS3 and HTML5 code snippets) that you can copy and paste into your code. Each pattern can be combined with other patterns to create an unlimited number of solutions, and each pattern works reliably in all major browsers without the need for browser hacks. The book is completely up-to-date with code, best practices, and browser compatibilities for HTML5 and CSS3?enabling you to dive in and make use of these new technologies in production environments. Pro HTML5 and CSS3 Design Patterns is so much more than just a cookbook, though! It systematically covers every usable feature of CSS3 and combines these features with HTML5 to create reusable patterns. Each pattern has an intuitive name to make it easy to find, remember, and refer to. Accessibility and best practices are carefully engineered into each design pattern, example, and source code. The book's layout, with a pattern's example on the left page and its explanation on the right, makes it easy to find a pattern and study it without having to flip between pages. The book is also readable from cover to cover, with topics building carefully upon previous topics. Pro HTML5 and CSS3 Design Patterns book unleashes your productivity and creativity in web design and development. Instead of hacking your way toward a solution, you'll learn how to predictably create successful designs every time by reusing and combining modular design patterns.
Title page; Copyright page; Contents at a Glance; Table of contents; About the Authors; About the Technical Reviewer; Acknowledgments; Introduction; Audience; Innovations; Six Box Models; Box Model Extents; Box Model Placement; Column Layouts; Fluid Layouts; Event Styling; Combining HTML5 and CSS3 to Create Design Patterns; Conventions; Using This Book; How This Book Is Structured; Downloading the Code; Using the Code; Contacting the Authors; CHAPTER 1 Design Patterns: Making CSS Easy!; Design Patterns-Structured Recipes; Using Design Patterns; Example 1-1. Background Image. Example 1-2. AbsoluteExample 1-3. Text Replacement; Example 1-4. Left Marginal; Example 1-5. Marginal Graphic Dropcap; Using Style Sheets; CSS Syntax; CSS Syntax Details; Using Whitespace in CSS; Using Property Values; Example 1-6. CSS Syntax Is Easy; Using Cascade Order; Example 1-7. Cascade Order; Simplifying the Cascade; CSS and HTML Links; Common CSS Properties; CSS Properties and Values: Common; CSS Properties and Values: Content; CSS Properties and Values: Layout; CSS Properties and Values: Specialized; Selectors; Media Queries; Flexible Units of Measure; Fixed Units of Measure. Ratios Between Units of Measure at 96 dpiTypical font-size Values at 96 dpi; Transitions, Animations, and 2D Transformations; Troubleshooting CSS; Normalized Style Sheet; CHAPTER 2 HTML Design Patterns; Chapter Outline; HTML Structure; HTML Structure; HTML; CSS; HTML Structure; XHTML; Valid XHTML; Valid HTML; XHTML; DOCTYPE; HTML; DOCTYPE; Header Elements; HTML; Header Elements; Conditional Style Sheet; HTML; CSS page.css; CSS ie6.css; Conditional Style Sheet; Structural Block Elements; HTML Pattern; Structural Block Elements; Terminal Block Elements; HTML; Terminal Block Elements. Multi-purpose Block ElementsHTML; Multi-purpose Block Elements; Inline Elements; HTML; Inline Elements; Class and ID Attributes; HTML; CSS; Class and ID Attributes; HTML Whitespace; HTML; CSS; HTML Whitespace; CHAPTER 3 CSS Selectors and Inheritance; Chapter Outline; Type, Class, and ID Selectors; HTML; CSS; Type, Class, and ID Selectors; Position and Group Selectors; HTML; Position and Group Selectors; Attribute Selectors; HTML; CSS; Attribute Selectors; Pseudo-element Selectors; HTML; CSS; Pseudo-element Selectors; Pseudo-class Selectors; HTML; CSS; Pseudo-class Selectors; Subclass Selector. HTMLCSS; Subclass Selector; Inheritance; HTML; CSS; Inheritance; Visual Inheritance; HTML; CSS; Visual Inheritance; CHAPTER 4 Box Models; Chapter Outline; Display; HTML; CSS; Display; Box Model; HTML; CSS; Box Model; Inline Box; HTML; CSS; Inline Box; Inline-Block Box; HTML; CSS; Inline-Block Box; Block Box; HTML; CSS; Block Box; Table Box; HTML; CSS; Table Box; Absolute Box; HTML; CSS; Absolute Box; Floated Box; HTML; CSS; Floated Box; CHAPTER 5 Box Model Extents; Chapter Outline; Width; CSS; Width; Height; CSS; Height; Sized; HTML; CSS; Sized; Shrinkwrapped; HTML; CSS; Shrinkwrapped.
Electronic reproduction.
Keywords: Computer science; Electronic books